Legal Protection of Contract Workers' Rights to Compensation in Cases of Premature Termination of Employment from The Perspective of Indonesian Positive Law - Shakilla Ardya Wardiyanto; Syaifuddin Zuhdi (Proceeding International Conference Restructuring and Transforming Law, 2026)
Premature termination of employment (PHK) of contract workers is a common problem in the Indonesian workforce. This problem can be detrimental to workers, both economically and legally, primarily due to the loss of income and the face of legal uncertainty. Although there are provisions in the law, in reality, legal protection for contract workers still faces various problems. This study aims to examine the rights of contract workers to receive compensation when their employment is terminated prematurely, from a legal perspective in Indonesia. In this study, the method used is a normative juridical method with a statutory and conceptual approach. Data were obtained by searching for information from laws and regulations, legal books, and scientific journal articles related to legal protection for contract workers who experience premature termination of employment. This study provides a more detailed explanation of the protection of contract workers' rights when experiencing premature termination, with a focus on the preventive and punitive aspects of protection, and analyzes the extent to which its implementation is effective in industrial relations practices in Indonesia. Research shows that legal protection for contract workers' rights is regulated in Law Number 13 of 2003, Law Number 6 of 2023, and Government Regulation Number 35 of 2021. Preventive protection is implemented by regulating the use of PKWT (Fixed-Term Work Agreements) and limiting termination of employment, while repressive protection is implemented by providing compensation and damages. However, the implementation of these protections has been inadequate due to violations by employers, lack of supervision, and workers' low legal understanding.